Absolute measurement of the generated aberrations from liquid crystal spatial light modulator using a common-path interferometry. Issue 13 (20th July 2017) - Bai, Fuzhong; Miao, Yue; Xu, Yongxiang; Wang, Geng; An, Ping
Abstract: A compact common-path interferometry is proposed to measure the wavefront aberration generated from liquid crystal spatial light modulator (LC-SLM). The LC-SLM is encoded with an aberration pattern and illuminated with a linearly polarized light oriented at ±45° with respect to the fast axis of liquid crystal, which is vertically oriented. The horizontal polarization component of the incident beam is not affected by the driving signal, while the vertical polarization component is modulated to the aberration loaded to the LC-SLM. By imposing a quarter-wave plate and a rotating analyzer, these two waves create four frames of phase-stepped interferograms. The aberration to be measured can be retrieved, and the result does not include any systematic error such as the substrate error of LC-SLM. Therefore, this method can implement absolute measurement, and help us to evaluate perfectly the fitting accuracy of the LC-SLM.